Destinasi Pariwisata Super Prioritas Likupang dan Pertumbuhan Ekonomi Kabupaten Minahasa Utara - Chrisna Riane Opod; Pradipta Mandasari Parasan; Irvandi Waraney Ombuh (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The growing tourism sector can bring much positive contribution to the economy, mainly in terms of income, GDP, generations of employment and economic growth. Likupang Super Priority Tourism Destination is located in North Minahasa Regency, North Sulawesi Province, has various potentials, uniqueness and attractions.The purpose of this study is to explore economic growth and the tourism sector in North Minahasa Regency, which is also explain its relations with the Likupang Super Priority Tourism Destination with a number potentials it has. This study uses a descriptive qualitative method, by conducting data tracing. Secondary data is the data used in this study. This study focuses on the Likupang Super Priority Destination, as well as North Minahasa Regency.The results of the study indicate that Tourism, in this case the development of the Likupang Super Priority Tourism Destination, has a number of potentials if developed properly. From data over several years, it can be concluded that economic growth in North Minahasa Regency has increased significantly in the years since the development of the Likupang DPSP began. By looking at the potential offered by the tourism sector for the regional economy, there is great hope that the development of the Likupang DPSP can provide a significant contribution to economic growth in North Minahasa Regency.